2005
DOI: 10.4319/lo.2005.50.4.1339
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of light on methane oxidation in the pelagic water column of a mesotrophic lake (Lake Biwa, Japan)

Abstract: Methane oxidation was studied in mesotrophic lake water (Lake Biwa, Japan) under thermally stratified conditions. Methane oxidation rates at in situ concentrations were very low in lake water from the epilimnion and thermocline but were high in hypolimnetic water. Incubation under light conditions ranging from 4.1 to 57 µmol photons m−2 s−1 resulted in decreased methane oxidation in hypolimnetic water. This inhibition was more severe as the light intensity increased. Addition of inorganic nitrogen (ammonium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 11 publications
(17 reference statements)
6
67
3
Order By: Relevance
“…The opposite diel patterns has been observed in a deeper wind-sheltered tropical lake which became stratified and accumulated CH4 in anoxic bottom water during daytime, while nighttime convection transported the accumulated CH4 to the surface waters resulting in elevated night-time emissions (Crill et al 1988). It has been suggested that methanotrophs could be inhibited by light (Dumestre et al 1999;Murase and Sugimoto 2005) but presumably this would have a limited effect on methane oxidation in surface sediments. The results from this study and the literature show that diel patterns in CH4 concentrations and diffusive fluxes cannot be ignored.…”
Section: Discussionmentioning
confidence: 98%
“…The opposite diel patterns has been observed in a deeper wind-sheltered tropical lake which became stratified and accumulated CH4 in anoxic bottom water during daytime, while nighttime convection transported the accumulated CH4 to the surface waters resulting in elevated night-time emissions (Crill et al 1988). It has been suggested that methanotrophs could be inhibited by light (Dumestre et al 1999;Murase and Sugimoto 2005) but presumably this would have a limited effect on methane oxidation in surface sediments. The results from this study and the literature show that diel patterns in CH4 concentrations and diffusive fluxes cannot be ignored.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, global estimates of CH 4 emissions from hydroelectric reservoirs that include downstream emissions (Lima et al, 2008;) calculated on the basis of the results from Amazonian reservoirs (Abril et al, 2005;Guérin et al, 2006;Kemenes et al, 2007) must be considered with caution as also pointed out by Narvenkar et al (2013).…”
Section: Contribution Of Downstream Emissions To Ch 4 Gross Emissionsmentioning
confidence: 99%
“…Each vial contained 60 mL of water and 100 mL of air. Vials were covered with aluminium foil to avoid the effect of light on any bacterial activity and incubated in the dark (Dumestre et al, 1999;Murase and Sugimoto, 2005) at 20 to 30 • C, depending on in situ temperatures. According to in situ concentration of CH 4 in the water, different amounts of CH 4 were added by syringe while withdrawing an equal volume of air from the headspace with a second syringe in order to obtain concentrations of dissolved CH 4 in the incubated water ranging from in situ to 4 times in situ.…”
Section: Aerobic Methane Oxidationmentioning
confidence: 99%
“…For methane to accumulate in the mid-water, it requires that methane oxidation is less than production. It has been proposed that methane oxidation is decreased by light in the photic zone (Murase and Sugimoto 2005); we therefore tested for this effect in Lake Stechlin.…”
mentioning
confidence: 99%